The Influence Of Word Of Mouth, Electronic Word Of Mouth, And Brand Image On Outpatient Decisions To Use Healthcare Services At Al-Muchtar Islamic Hospital Karawang - Syafitri, Resty Dian; Rinaldi, Enrico Adhitya; Ambarini, Tinon; Agustin, Dinni (Journal of Ageing And Family, 2024)
Background : Hospitals have become public healthcare service facilities that are not only socially oriented but also have a business aspect. The increasing competition among healthcare service facilities requires hospitals to pay attention to the factors that influence, guide, and encourage patients' decisions in choosing a hospital, including word of mouth (WOM), eWOM, and brand image. This study aims to determine the influence of WOM, eWOM, and brand image on the decision to choose outpatient services at AlMuchtar Islamic Hospital in Karawang. The research was conducted using a quantitative method with a cross-sectional approach. Data was collected by distributing questionnaires to respondents. The sampling technique used was purposive sampling, which involved distributing questionnaires to respondents who were available at a certain place according to the context of the research.. Hypothesis testing was conducted using t-tests and F-tests. The results of the study show that there is an influence of word of mouth and brand image on the decision to choose outpatient services at the hospital, while the eWOM variable does not have a significant effect. Result :Therefore, it can be concluded that word of mouth (WOM) and brand image play an important role in the decision to choose outpatient services at AlMuchtar Islamic Hospital in Karawang. Keywords: Word of Mouth, eWOM, Brand Image, Decision to Choose Healthcare Services